2021
DOI: 10.1590/1678-4324-75years-2021200772
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus cinerea: Microscopic Profile, Chemical Composition of Essential Oil and its Antioxidant, Microbiological and Cytotoxic Activities

Abstract: Eucalyptus species possess anti-inflammatory, antifungal, antibacterial, and insecticidal properties. In this study, the chemical composition and biological activities of Eucalyptus cinerea essential oil HIGHLIGHTS  Eucalyptus cinerea essential oil (EO) contains 1,8-cineole as the main component.  This EO demonstrated antioxidant and antimicrobial properties.  This EO reduced the viability of Jurkat and Calu-3 cells and decreased DNA content. This EO had cell death mechanism related to apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The chemical composition of the crystals occurring in plants can be identified using EDS 40 , 41 . In the present study, four morphotypes of calcium oxalate crystals were found in various tissues of V. album subsp.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of the crystals occurring in plants can be identified using EDS 40 , 41 . In the present study, four morphotypes of calcium oxalate crystals were found in various tissues of V. album subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium oxalate crystals are frequently found in different tissues and organs of plants (Brito et al, 2021; Horner et al, 2012; Horner & Wagner, 1995; Pauzer et al, 2021). They present a great diversity of morphologies, such as prisms of different shapes, druses, styloids, and crystal sands, and are helpful in species identification (Upton et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, other compositions can also occur, such as calcium carbonate (CaCO 3 ) crystals, or even silica crystals (SiO 2 ) (Bosqueiro, 1995;Webb, 1999). Crystals in plants have been reported as calcium oxalate using EDS in many studies (Lersten & Horner, 2011;Saulle et al, 2018;Santos et al, 2018;Almeida et al, 2020;Klider et al, 2020;Brito et al, 2021;D'Almeida et al, 2021;Pauzer et al, 2021;Gribner et al, 2022). Only a few studies have reported calcium sulfate crystals (Storey & Thomson, 1994;Pritchard et al, 2000;He et al, 2012).…”
Section: Morphology and Distribution Of Crystalsmentioning
confidence: 99%